2019
DOI: 10.1158/1538-7445.sabcs18-p5-03-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-03-04: Targeting the tumor microenvironment by CXCR4 inhibition to abrogate trastuzumab resistance in HER2-positive breast cancer

Abstract: Background: Despite the fact that trastuzumab alongwithotherHER2-targetingdrugshavesignificantlyimprovedthe survival of patients with HER2 overexpression breast cancers (HER2+BC), resistance to trastuzumab is a clinical challenge in HER2+BC. Discerning actionable mechanisms of resistance to trastuzumab remains an important unmet need. WepreviouslyreporteddysregulationofCXCR4involvedintrastuzumab-resistance,butitscausal roleandthe associated mechanismsremainunknown. Methods We established trastuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…In our previous studies, by establishing and using trastuzumab-resistant breast cancer cell models, we initially found upregulation of C-X-C motif chemokine receptor 4 (CXCR4), a G protein-coupled receptor of stromal cell-derived factor-1 (SDF-1; CXCL12) in trastuzumab-resistant breast cancer. Knockdown of CXCR4 with shRNA sensitized the cells to trastuzumab [18][19][20]. Consistent with our ndings, a very recent clinical study showed increased CXCR4 expression in trastuzumab-resistant breast cancer tissues and was associated with a higher risk of recurrence [21].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our previous studies, by establishing and using trastuzumab-resistant breast cancer cell models, we initially found upregulation of C-X-C motif chemokine receptor 4 (CXCR4), a G protein-coupled receptor of stromal cell-derived factor-1 (SDF-1; CXCL12) in trastuzumab-resistant breast cancer. Knockdown of CXCR4 with shRNA sensitized the cells to trastuzumab [18][19][20]. Consistent with our ndings, a very recent clinical study showed increased CXCR4 expression in trastuzumab-resistant breast cancer tissues and was associated with a higher risk of recurrence [21].…”
Section: Introductionsupporting
confidence: 88%
“…We previously showed upregulation of CXCR4 is involved as a driver of trastuzumab resistance in HER2+ breast cancer cells [18][19][20]. In the current study, we demonstrated that the increased CXCR4 expression is associated with cell cycle progression and reaches a peak in the G2/M phases.…”
Section: Discussionsupporting
confidence: 62%
“…Amplification or mutation of HER2 and upregulation of downstream PI3K/AKT and MAPK pathway are usually proposed as the mechanism of drug resistance [ 9 17 ]. We previously reported that CXCR4 is involved as a driver of trastuzumab resistance in HER2 + breast cancer cells [ 18 – 20 ] with an unknown mechanism. In the current study, we demonstrated that the increased CXCR4 expression in trastuzumab-resistant tumor cells is associated with cell cycle progression and reaches a peak in the G2/M phases, contributing to cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, by establishing and using trastuzumab-resistant breast cancer cell models, we initially found upregulation of C-X-C motif chemokine receptor 4 (CXCR4), a G protein-coupled receptor (GPCR) of stromal cell-derived factor-1 (SDF-1α; CXCL12) in trastuzumab-resistant breast cancer. Knockdown of CXCR4 with shRNA sensitized the cells to trastuzumab [ 18 – 20 ]. Consistent with our findings, a very recent clinical study showed increased CXCR4 expression in trastuzumab-resistant breast cancer tissues and was associated with a higher risk of recurrence [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…CXCR4 activation is additionally associated with endocrine therapy resistance through the downregulation of estrogen receptor expression (30). CXCR4 signaling is implicated in other areas of drug resistance: In breast cancer, CXCR4 silencing sensitizes TNBC cells to cisplatin therapy (31), silencing of CXCR4 and SDF-1 sensitizes breast cancer cells to paclitaxel (32), and CXCR4 inhibition abrogates trastuzumab resistance in HER2-positive breast cancer (33). We previously demonstrated that CXCR4 expression mediates estrogen-independent tumorigenesis, metastasis, and resistance to endocrine therapies through increased MAPK signaling (34,35).…”
Section: Introductionmentioning
confidence: 99%